REVENGE REFLECTED IN AGATHA CHRISTIE’S MURDER ON THE ORIENT EXPRESS NOVEL (1934): PSYCHOANALYTIC APPROACH - Yasmine, Aliffia (Jurusan Sastra Indonesia, 2023)
This research describes Linda Arden's revenge on Agatha Christie's novel entitled Murder on The Orient Express. The method of data collection is descriptive qualitative research. Based on the analysis, the researcher gets some conclusions. First, the main motive of Linda Arden's revenge is the kidnapping case of her granddaughter, Daisy, who was not only kidnapped but also killed by Cassetti, followed by the death of her daughter, Sonia, and son-in-law, Colonel Armstrong and also the death of Susanne, Daisy's nursemaid. Second, the revenge that Linda Arden planned is to end Cassetti's life with the help of the others affected by Cassetti's crime.